Prospective longitudinal comparative study showed that breastfeeding outcomes were comparable in preterm twins and singleton infants - Tandberg Bente Silnes; Grundt Hege; Moen Atle; Niela-Vilén Hannakaisa; Flacking Renée (Wiley-Blackwell Publishing Ltd., 2025)
AIM
We compared milk volumes, skin-to-skin contact and breastfeeding by the mothers of very preterm twins and singleton infants born at 28-32 weeks of gestation.
METHODS
This Norwegian longitudinal prospective comparative study was carried out in two neonatal intensive care units: one with single family rooms and one open bay unit. It comprised 49 singleton infants, 28 twins and their mothers. The mothers' milk volume and direct breastfeeding were recorded from birth until 4 months' of corrected age. They also answered the breastfeeding self-efficacy scale and skin-to-skin contact was recorded.
RESULTS
The mothers of preterm twins produced doubled the volume of expressed milk at day 14, compared to the mothers of singletons (mean 816 ± 430 mL vs. 482 ± 372 mL, p < 0.05) and this difference was still sustained at 34 + 0 weeks/days (p < 0.02). Mothers of twins had their first breastfeeding attempt later than mothers of singletons (median of 133 h compared to 56 (p < 0.002). Preterm twins received less daily skin-to-skin contact (mean 157 ± 66 min each vs. 244 ± 109) (p < 0.001). There were no differences in receiving mother's own milk, exclusively direct breastfeeding or perceived breastfeeding self-efficacy.
CONCLUSION
Breastfeeding was initiated as successfully in preterm twins as singletons as the mothers' milk production doubled.